Impact of mobile phone text messaging intervention on adherence among patients with diabetes in a rural setting: A randomized controlled trial - Owolabi, Eyitayo Omolara (Medicine (Baltimore), 2020)
BACKGROUND: Nonadherence to prescribed therapy is a significant challenge at the primary healthcare level of South Africa. There are documented evidence of the potential impact of mobile health technology in improving adherence and compliance to treatment. This study assessed the effect of unidirectional text messaging on adherence to dietary and activity regimens among adults living with diabetes in a rural setting of Eastern Cape, South Africa. METHODS: This was a 2-arm, multicenter, parallel, randomized controlled trial, involving a total of 216 patients with diabetes with uncontrolled glycemic status randomly assigned into the intervention (n = 108) and the control group (n = 108). Participants in the intervention arm received daily educational text messages on diabetes and reminders for 6 months, while the control arm continued with standard care only. A validated, self-developed adherence scale was used to assess participants’ adherence to diets and physical activity. Descriptive statistics and linear regression were used to assess changes in adherence and the effect of the intervention on adherence to therapy. RESULTS: On a scale of 8, the mean medication adherence level for the intervention group was 6.90 (SD ± 1.34) while that of the control group was 6.87 (SD ± 1.32) with no statistical difference (P = .88). The adjusted mean change in the medication adherence level was 0.02 (−0.33 to 0.43) with no significant difference (P = .79). There was however a low level of adherence to dietary recommendations (1.52 ± 1.62), and physical activity (1.48 ± 1.58) at baseline, and both groups demonstrated a nonsignificant increase in dietary (P = .98) and physical activity adherence (P = .99) from baseline to the follow-up period. CONCLUSION: There is a moderate level of adherence to medication and a low level of adherence to dietary and physical activity recommendation in this setting. The text messaging intervention did not bring about any significant improvement in medication, dietary and physical activity adherence levels. There is a need to design effective strategies for improving adherence to recommended lifestyle changes in this setting.